2018
DOI: 10.1111/his.13488
|View full text |Cite
|
Sign up to set email alerts
|

Primordial odontogenic tumour: report of two cases

Abstract: This report describes two additional cases of POT for a total of 11 cases reported in the English language literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 14 publications
3
34
3
Order By: Relevance
“…The clinical and radiographic data were available in the charts of the patient. The literature review included six articles of POT previously reported in the English-language literature [1,[8][9][10][11][12]. Thus, to the best of our knowledge, only 12 cases of POT have been reported to date, all of them affecting patients in the first two decades of life ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical and radiographic data were available in the charts of the patient. The literature review included six articles of POT previously reported in the English-language literature [1,[8][9][10][11][12]. Thus, to the best of our knowledge, only 12 cases of POT have been reported to date, all of them affecting patients in the first two decades of life ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The term POT was first proposed by Mosqueda-Taylor et al [1], who reported a series of six cases of a previously undescribed odontogenic tumor with features similar to primitive dental papilla and follicle, arising in areas of missing or unerupted teeth of patients before adult life. Since then, six additional cases have been identified in the English-language literature [8][9][10][11][12]. We present an additional case in order to contribute to a better classification and understanding of this rare odontogenic tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some issues about POT remain unclear and require future reports. The description of the odontogenic epithelium covering the ectomesenchyme was often contradictory, while it remains debatable whether peripheral ameloblastic islands or hard dental tissue deposition can occasionally occur within the tumor [3,4].…”
Section: Discussionmentioning
confidence: 99%